Demographic profiling of poisoning in Emergency Department of Kathmandu Medical College - A cross sectional study - Kushwaha, Anu; Singh, Pankaj Kumar (Journal of Kathmandu Medical College, 2018)
Background: Poisoning is a very common medico-social problem in our part of the world. It significantly contributes to the morbidity and mortality, which is a big concern and burden to our society.Objective: To determine the demographic profiling of poisoning in Emergency Department of Kathmandu Medical College.Methododogy: This is a cross sectional study conducted for the period of six months from March 2017 to September 2017 at the Emergency Department Kathmandu medical college teaching hospital. The study includes the cases of poisoning brought to the above mentioned institute for management. The data thus collected was entered in the SPSS and analysed to find the poisoning profile. Ethical clearance was taken from Institutional Review Board of Kathmandu Medical College.Results: A total of 40 cases of poisoning came to Emergency Department over the period of six months of which 14 (35%) were males and 26 (65%) were females. The mean ages for males were 32.07 years and females were 26.23 years. Regarding time of consumption 42.5% of cases consumed poison at night. The most common poison consumed was Organophosphorus (55%) and next in kin was paracetamol (15%). However, type of Organophosphorus could not ascertained due to lack of information from the patent party.Conclusion: People in the productive age groups are more prone to poisoning with various products due to stress or other social economic factors. Social education and strict rules and regulation for the sale of the pesticides can be useful in containing this problem.